Idiopathic Granulomatous Mastitis and Elastosis Perforans Serpiginosa: An Undescribed Association. (21st September 2018) - Ibarra, Alvaro; Valenzuela, Fernando; Arancibia, Patricia; Flores, Edwin; Aparicio, Sergio; Paredes, Hernando; Segovia, Jorge
Abstract: Introduction: Elastosis perforans serpiginosa (EPS) is a very rare perforating dermatosis, in which abnormal elastic fibers and other connective tissue components are eliminated from the dermis, through the epidermis. The majority of cases are idiopathic or related to systemic diseases. Exceptional cases associated with penicillamine have had extracutaneous involvement. Idiopathic granulomatous mastitis (IGM) is a rare chronic granulomatous inflammation. Clinically, it can simulate carcinoma. Their images are nonspecific but eventually suspicious. No concomitance of EPS and IGM has been described. Clinical Case and Results: A 40-year-old woman with a history of type 2 diabetes mellitus who had a 5-month-long left side mastitis with cutaneous fistulae was treated with an empiric antibiotic regimen. A breast biopsy disclosed an IGM. Ultrasound studies showed laminar collections in the breast tissue. Cultures, B hensellae and Lues serologies, and M tuberculosis complex PCR were negative. A biopsy of a fistula orifice revealed a noncaseating granulomatous process. Histochemical stains (PAS, Grocott, Ziehl-Neelsen) and B hensellae immunostain were negative. Histochemical orcein stain demonstrated the presence of coarse elastic fibers within granulomata. The same stain performed in the breast biopsy showed normal elastic fibers. She was treated with surgical drainages and topical corticosteroids, with almost complete regression of the lesions after 5 months of follow-up. Conclusions: We present a case of idiopathic granulomatous mastitis associated with elastosis perforans serpiginosa, not previously described. The EPS appears to be related to diabetes mellitus. This degenerative dermatosis tends to be located in areas with repeated mechanical injury. It is hypothesized that the damage of the epidermal barrier or an alteration of elastic fibers might be initiating factors. IGM fistulae may have triggered this clinical picture. Both processes share a granulomatous morphology, but the status of the elastic fibers in the breast and the skin confirms their different nature.